Tomatoland : how modern industrial agriculture destroyed our most alluring fruit - Estabrook, Barry (Kansas City : Andrews McMeel Publishing, 2011)
Investigative food journalist Barry Estabrook reveals the huge human and environmental cost of the $5 billion fresh tomato industry and the price we pay as a society when we take taste and thought out of our food purchases.
On the tomato trail -- Roots -- A tomato grows in Florida -- Chemical warfare -- From the hands of a slave -- An unfair fight -- A penny per pound -- Matters of taste -- Building a better tomato -- Tomatoman -- Wild things.
Includes bibliographical references (p. 194-206) and index.
Keywords: Tomatoes -- Biotechnology; Tomatoes; Agriculture -- Environmental aspects; Agricultural ecology